2019
DOI: 10.1101/606186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Redox potential defines functional states of adult hippocampal stem cells

Abstract: Intracellular redox states regulate the balance between stem cell maintenance and activation. Increased levels of reactive oxygen species (ROS) are linked to proliferation and lineage specification. In contrast to this general principle, we show that in the hippocampus of adult mice it is the quiescent neural stem cells (NSCs) that maintain the highest ROS levels (hiROS). Classifying NSCs based on intracellular ROS content identified subpopulations with distinct molecular profiles, corresponding to functional … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 85 publications
1
5
0
Order By: Relevance
“…In general, quiescent NSCs are thought to have higher ROS levels, which gradually decrease during the progenitor stage, with low levels of ROS reported in mature neurons [128]. A recent study in mice suggested that NSCs require a spike in ROS levels before committing to proliferation and that this induction is prior to the redirection of cellular lipid metabolism to lipogenesis or induction of mitochondrial biogenesis [142]. Interestingly, the authors also suggested that NSCs can shift between different levels of proliferation induction, depending on ROS levels, without fully committing to enter neurogenesis [142].…”
Section: Redox State and Rosmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, quiescent NSCs are thought to have higher ROS levels, which gradually decrease during the progenitor stage, with low levels of ROS reported in mature neurons [128]. A recent study in mice suggested that NSCs require a spike in ROS levels before committing to proliferation and that this induction is prior to the redirection of cellular lipid metabolism to lipogenesis or induction of mitochondrial biogenesis [142]. Interestingly, the authors also suggested that NSCs can shift between different levels of proliferation induction, depending on ROS levels, without fully committing to enter neurogenesis [142].…”
Section: Redox State and Rosmentioning
confidence: 99%
“…A recent study in mice suggested that NSCs require a spike in ROS levels before committing to proliferation and that this induction is prior to the redirection of cellular lipid metabolism to lipogenesis or induction of mitochondrial biogenesis [142]. Interestingly, the authors also suggested that NSCs can shift between different levels of proliferation induction, depending on ROS levels, without fully committing to enter neurogenesis [142]. It is therefore likely that multiple signals have to come together to initiate neurogenesis.…”
Section: Redox State and Rosmentioning
confidence: 99%
“…Shifts to lower ROS content primed NPCs to a subsequent state transition, showing that lower ROS levels correlated with increased expression of proliferation and differentiation genes. In addition, NOX2 was not necessary for NPCs proliferation under physiological conditions, even if it has been reported that a transient NOX2-dependent ROS burst promotes exercise-induced recruitment of qNSCs to proliferation (Adusumilli et al, 2021). While this evidence seems to be in contrast with previous ones, they may not be mutually exclusive, because the transient nature of ROS and ROS signals likely triggers cell transitions without substantially altering ROS levels in the next cell type, especially if the ROS burst also activates antioxidative genes (Bueler, 2021).…”
Section: Ros Modulation Of Adult Neurogenesismentioning
confidence: 85%
“…However, given that the mechanisms underlying the high glucose-induced impairment of cell differentiation remain poorly understood, the application of PDLSCs to promote periodontal tissue regeneration in patients with diabetes is still in its infancy. Recently, increasing evidence has suggested that ROS play a vital role in the regulation of cell differentiation (17,18). Many studies also found that cells incubated under high glucose conditions showed dysregulation of intracellular ROS and NADPH, indicating that they might contribute to high glucoseinduced cellular osteogenic differentiation impairment (29, 36).…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms involved are still mysterious, but studies have revealed that the high glucose-caused cell dysfunction may be associated with inhibition of Glo1/AGE/RAGE axis (14), PI3K/Akt pathway (15), activation of MAPK pathway (13), excessive generation of reactive oxygen species (ROS) (16) and so on. Among the mechanisms studied, ROS, small molecules derived from oxygen and participate in regulating cell fate and cell proliferation and differentiation (17,18), has been recognized to be the most important contributor, and would be a potential target for periodontal treatment (19)(20)(21). Generally, increased ROS accumulation was found to be responsible for the reduced osteogenic differentiation potential of stem cells (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%